What fundamentals drive world migration? - Timothy J. Hatton; Jeffrey G. Williamson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Governments in the OECD note rising immigration with alarm and grapple with policies aimed at selecting certain migrants and keeping out others. Economists appear to be well armed to advise governments since they are responsible for an impressive literature that examines the characteristics of individual immigrants, their absorption and the consequences of their migration on both sending and receiving regions. Economists are, however, much less well armed to speak to the determinants of the world migrations that give rise to public alarm. This paper offers a quantitative assessment of the economic and demographic fundamentals that have driven and are driving world migration, across different historical epochs and around the world. The paper is organized around three questions: How do the standard theories of migration perform when confronted with evidence drawn from more than a century of world migration experience? How do inequality and poverty influence world migration? Is it useful to distinguish between migration pressure and migration ex post, or between the potential demand for visas and the actual use of them? – migration ; poverty ; demographic economics ; emigration ; immigration
Keywords: F22; J1; O15; 330; Internationale Wanderung; Welt; Migrationstheorie